Evaluation of Patients Presenting to Pediatric Emergency Department using a Ground Ambulance - Ali Güngör; Damla Hanalioğlu; Necati Emrecan Türk; Arif İsmet Çatak (Galenos Yayinevi, 2020)
Introduction:Emergency departments are 24-hour open health services. Patients can register to the emergency departments by their own or via emergency ambulance services (EAS). In this study, we aimed to examine the characteristics of patients who were admitted to a pediatric emergency department via EAS and to evaluate clinical and laboratory data of the patients as well as their managements during hospital stay .Methods:Patients brought to the emergency department via EAS between 1 June 2017 and 30 December 2017 were retrospectively analyzed. Data on demographic characteristic and presenting complaints of the patients and resources used were collected.Results:A total of 1234 patients (631 males, 51.1%) were included in the study. The median age of the patients was 75 months (Interquartile range 24-162 months). The majority of patients (n=514, %42) were admitted to the emergency department between the hours 16.01 and 23.59. The most common complaints were convulsion in 231 patients (18.7%), fever in 139 (11.3%), abdominal pain in 129 (10.4%), and intoxication in 86 (6.97%). We noticed that patients used EAS for non-urgent complaints such as constipation, toothache, red eye, nasal discharge, leg pain, leg tenderness, sore throat, and skin rashes and eruptions. No laboratory tests were necessary for 207 patients (17.8%), and 690 patients (56%) did not require hospitalization.Conclusion:There were various reasons for calling ambulances but it was found that families called ambulances for non-urgent complaints such as constipation, toothache, redness in eye and nasal discharge. For this reason, it is necessary to improve the public awareness of the role of ambulance services in order to minimize unnecessary use of ambulance transportation.